Assisting science teachers in developing augmented reality media to improve students’ critical and creative thinking - Sri Wahyuni; Iin Hindun; N. Nurwidodo (Journal of Community Service and Empowerment, 2025)
Augmented Reality (AR) is a cutting-edge educational tool that effectively visualizes invisible or abstract objects, such as internal human organs or plant anatomy. However, developing AR media requires specific skills and knowledge, which many teachers lack. This community service project aimed to assist science teachers at SMA Muhammadiyah 3 Kota Batu in designing and utilizing AR media to enhance students' critical and creative thinking. The method involved a series of activities including awareness sessions, workshops, mentoring, implementation, and evaluation. As a result, participating teachers gained knowledge and skills in AR development, produced simple AR media, and successfully integrated it into the learning process. The project significantly contributed to the teachers’ professional development and supported the digital school program. The main outputs include AR media prototypes, published articles, and broader media dissemination.